Analysis of the Phenomenon of Acute Respiratory Infection (ARI) in Children Under Five at the Boyolali Regency Regional Health Center - Sri Suparti (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2025)
Boyolali is located at the foot of Mount Merapi, and characterized by a cold, humid climate with an average temperature of 20°C. Acute Respiratory Infections (ARI) affect the upper and lower respiratory tracts for less than 14 days and are caused by viruses, bacteria, or fungi. ARI remains among the top three causes of illness in Central Java. This study aims to analyze individual and environmental factors contributing of ARI incidence in children under five years of age. An observational cross-sectional design was employed, with data collected through questionnaires. The number of children under 5 years old recorded was 109,968, resulting in a minimum sample size of 383. Questionnaires were distributed across 6 service areas of the Boyolali Public Health Center. Data analysis used binary logistic regression techniques. Results: ARI in infants (sig < 0.05). The odds ratio is 4.307. This means that infants with good individual factors will increase the number of non-ARI infants by 4.307 times. Environmental factors in infants (sig < 0.05). The odds ratio is 152.660. This means that infants with favorable environmental factors will increase of non-ARI infants by 152.660 times. Based on the results of the Spearman correlation test. Individual factors are important in environmental factors. Conclusion: In this study, both individual factors and environmental conditions significantly influence the incidence of ARI in infants in the Puskesmas in Boyolali.Keywords: Acute Respiratory Infections, Analysis, Children, Risk Factors